CTL Based Pocket Book to Improve Fourth Grade Elementary School Students’ Learning Outcomes in Pancasila Education - wahyushafa88 shafa; Rudi Erwandi; Tio Gusti Satria (Jurnal Elementaria Edukasia, 2026)
This study aims to determine the completeness of student learning outcomes after the implementation of a pocket book based on Contextual Teaching and Learning in the Pancasila Education subject for fourth-grade students of SD Negeri 2 Tegalrejo. This type of research is Research and Development (R&D) and the research method used is the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. Using a pre-test and post-test research design, with 10 multiple-choice questions. The research subjects were 22 fourth-grade students and teachers of SD Negeri 2 Tegalrejo. Data collection techniques consisted of documentation, questionnaires, and tests. Data analysis techniques consisted of a pocket book validity test, a test of validity and reliability of instrument test questions, a practicality test, and an effectiveness test. The results of the study indicate that the developed Pancasila Education pocket book has met the valid criteria based on the assessment of language, media, and material experts. In addition, the Pancasila Education pocket book was also declared practical based on teacher and student responses. In addition to being effective in improving student learning outcomes on the material on the values ​​and meaning of Pancasila, this pocket book on Pancasila education based on Contextual Teaching and Learning is suitable for use as teaching material for Pancasila education in elementary schools.